Pengaruh Financial Distress Dan Leverage Terhadap Fleksibilitas Klasifikasi Arus Kas - Retno Istiani; Nurzi Sebrina; Halmawati Halmawati (Universitas Negeri Padang, 2020)
This study aims to provide empirical evidence regarding the effect of financial distress and leverage on the flexibility in cash flow classification in nonfinancial companies listed on the Indonesia Stock Exchange in 2017-2018. The flexibility in cash flow classification is where managers are allowed to classify interest paid, interest received, and dividend received into operating, investing, or financing cash flow activities. By using purposive sampling method, obtained research samples of 395 companies. In this study, the flexibility of cash flow classification measured by dummy method of utilizing the cash flow classification flexibility by manager. this reseach create a poxy for financial distress based on Altman's Z-score (Altmant and Hotchkiss, 2006), while leverage measured by debt to total assets ratio. Analysis technique used logistic regression analysis. The results showed that financial distress has no effect on flexibility in cash flow classification. Leverage has a positive and significant effect on flexibility in cash flow classification, which is firm with high leverage tend to take advantage cash flow classification flexibility to infale operating cash flow